Ultrafast Sintering for Ceramic‐Based All‐Solid‐State Lithium‐Metal Batteries. Issue 33 (13th July 2022) - Chen, Shaojie; Nie, Lu; Hu, Xiangchen; Zhang, Yining; Zhang, Yue; Yu, Yi; Liu, Wei
Abstract: Long processing time and high temperatures are often required in sintering ceramic electrolytes, which lead to volatile element loss and high cost. Here, an ultrafast sintering method of microwave‐induced carbothermal shock to fabricate various ceramic electrolytes in seconds is reported. Furthermore, it is also possible to integrate the electrode and electrolyte in one step by simultaneous co‐sintering. Based on this ultrafast co‐sintering technique, an all‐solid‐state lithium‐metal battery with a high areal capacity is successfully achieved, realizing a promising electrochemical performance at room temperature. This method can extend to other various ceramic multilayer‐based solid devices. Abstract : A microwave‐assisted ultrafast sintering technique is used to densify various ceramic electrolytes and co‐sinter electrode–electrolyte integration, which has advantages of ultrashort sintering time (≈25 s), energy‐saving, suppressed Li/Na element loss, compact electrode–electrolyte interface, restrained element cross‐diffusion, and so on. This method may extend to other ceramic multilayer‐based solid devices.